2020
DOI: 10.2495/arc200131
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Habitat in Burkina Faso: Social Trajectories, Logics and Motivations for the Use of Compressed Earth Blocks for Housing Construction in Ouagadougou

Abstract: This study explores the logics, motivations and issues related to the construction of sustainable housing made of compressed earth blocks (CEB) material in the city of Ouagadougou. In Burkina Faso, a landlocked country with limited natural resources and predominantly warm dry climate, most buildings are made of local materials. Historically, people built their habitats using mud brick (adobe). However, with the irreversible process of urbanization, the construction sector recorded changes with an increase in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In sum, while CEB construction is halfway between traditional and modern building cultures, the owners of CEB housing in the Burkinabe context have a more positive perception of the material. This has been already pointed out in a recent study: the particular way of house construction using CEB by the fraction of population in Ouagadougou integrates the current logic of sustainability in the construction sector (Zoungrana et al, 2020). This same finding is also highlighted in a similar study conducted in North Carolina, Piedmont, which showed that the contractors who had experienced with CEB have a positive perception than those without the prior experience of CEB (Hughes et al, 2017).…”
Section: Post-materialistic Representations Of Construction Using Cebsupporting
confidence: 70%
“…In sum, while CEB construction is halfway between traditional and modern building cultures, the owners of CEB housing in the Burkinabe context have a more positive perception of the material. This has been already pointed out in a recent study: the particular way of house construction using CEB by the fraction of population in Ouagadougou integrates the current logic of sustainability in the construction sector (Zoungrana et al, 2020). This same finding is also highlighted in a similar study conducted in North Carolina, Piedmont, which showed that the contractors who had experienced with CEB have a positive perception than those without the prior experience of CEB (Hughes et al, 2017).…”
Section: Post-materialistic Representations Of Construction Using Cebsupporting
confidence: 70%
“…In developing countries such as Burkina Faso, construction with earthen materials should represent a suitable solution for the problem of sustainable housing for the population since it is cheap and so-called sustainable. The socioeconomic impact of constructions based on earthen materials in the context of Burkina Faso has been studied by authors such as Zoungrana, and it confirms the eco-friendly status of raw earth construction materials [7][8][9]. Furthermore, earthen materials such as LS present very good comfort properties for Sahelian cities, villages, and hot environments due to their hygrothermal properties [10][11][12][13].…”
Section: Introductionmentioning
confidence: 85%
“…The improvement of the durability performances of earthen materials, and more specifically compressed earth blocks (CEBs) is essential for their widespread adoption in the building construction [1], [2]. Numbers of studies have reported that the different stabilisation using chemical industrial binders: cement and lime or alternative/by-product binders: geopolymer, lime residue or riche husk ash improve various engineering and durability indicators of CEBs [3]- [7].…”
Section: Introductionmentioning
confidence: 99%